Pengaruh Pressure Drop terhadap Efektivitas Heat Exchanger Dengan Menggunakan Simulator Aspen Hysys V. 7.3 - Widya Rahma Iswara (Seminar Nasional Teknik Kimia Kejuangan, 2015)
Heat Exchanger is a device that used to exchange the heat between the fluids that had higher temperature to the fluid with lower temperatures. One type of heat exchanger that often used is the heat exchanger Shell and Tube. In the simulation analyzed the influence of heat duty and enthalpy to temperature, fluid temperature variation being used for the shell side range 87-92oC, for the tube side 25-50oC, and analyzed the effect of pressure drop on the fouling factor with simulator Aspen Hysys v.7.3. According to the results, it is found that the pressure drop on the shell side has passed the permissible value from base design, it means that the shell side already requires to cleaned, while the tube side pressure drop values exist under the conditions allowed by the base design, it means that the tube side is in good condition, and for the effect of heat flow to the temperature is when the value of the difference temperature higher , the heat flow generated value will be higher, and the value of the enthalpy is also proportional to the temperature value.